Pengaruh leverage, likuiditas, dan profitabilitas terhadap agresivitas pajak (Studi pada perusahaan sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia tahun 2019-2022) - Grace Ezra Aulia Deborah Simanungkalit; Novi Swandari Budiarso; Claudia Korompis (Yayasan Widyantara Nawasena Raharja, 2023)
Companies often view tax as a burden that reduces net profit, resulting in them tending to take action to minimize the tax burden or what is called tax aggressiveness. Several factors that can influence tax aggressiveness are leverage . liquidity , and profitability. The aim of this research is to determine the influence of Leverage , Liquidity and Profitability on Tax Aggressiveness in Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2019 - 2022. Leverage is measured using the debt to assets ratio calculation , liquidity is measured using the current ratio calculation , profitability is measured using the return on assets calculation , and tax aggressiveness is measured using the effective tax rate . This type of research is quantitative research with a sampling technique, namely purposive sampling consisting of 30 samples from 51 populations and using multiple linear regression analysis with data processing via IBM SPSS 26. Partial and simultaneous research results show that leverage , liquidity and profitability have an influence against tax aggressiveness.